How to survey education for cross-national comparisons - Hoffmeyer-Zlotnik, Jürgen H. P. (Metodološki zvezki, 2007)
Social surveys collect information on socio-demographic characteristics of respondents eligible for the interview. Among others, the highest attained level of education is one of the variables explaining the respondent's social and political comportment, the interviewee's human values and orientations, the transition from school to work, the position in the labor force and its segments, the social and economic behavior of the individual actor and structural inequalities in modern societies. Manifold strategies to operationalize the qualification and education variables during interviews can be observed in social surveys. They differ in the underlying latent concept captured, the ranking and classifying of levels into categories and clusters, the degree of classification and measurement details and finally the capabilities of comparison across time and across nations and cultures. The measurement of education for comparative research across countries is a complex task. The national systems of education and schooling are differently organized across the nations. Altogether four different types of school and training systems can be identified in Europe. In this paper we will sort the national certificates from general and vocational schools into one matrix, the newly developed Hoffmeyer-Zlotnik/Warner-matrix of education. This matrix allows us to compare the highest level of education a person has reached, as a combination of general and vocational education and useable for a person to obtain a starting position on the labor market. This article discusses those measurement instruments normally used in international comparative surveys and introduces the Hoffmeyer-Zlotnik/Warner-matrix of education, contrasting this matrix with the other established measurement instruments. To demonstrate the validity of our matrix, we show the advantages of our matrix exemplified in one case from nations out of the four types of different educational systems: Germany, Luxembourg, Denmark, and France.
Keywords: Educational systems; Izobraževalni sistemi; Izobraževanje; Education; Measurement; Merjenje; Instrumentalism; Instrumentalizem; Matrices; Matrike; Klasifikacija; Classification; Comparative research; Primerjalne raziskave; Nemčija; Germany; Luksemburg; Luxembourg; Danska; Denmark; France; Francija; raziskovalne metode; mednarodne primerjave